In vitro generation of lymphocytotoxicity to autochthonous leukaemic cells in chronic myeloid leukaemia. - Khare, A. G. (Nature Publishing Group, 1981)
Lymphocytes from 13 chronic myeloid leukaemia (CML) patients in remission were tested for their ability to differentiate in vitro into a cell population cytotoxic to autochthonous target leukaemic cells. CML remission lymphocytes were cultured in vitro with autochthonous leukaemic cells and allogeneic normal lymphocytes from an unrelated donor, singly or in combination. The cytotoxic lymphocytes obtained after 7 days of culture were tested for their ability to kill autochthonous leukaemic cells in a 3h 51Cr-release assay. It was found that with the allogeneic stimulus alone, cytotoxicity was generated in 5/13 cases, whilst stimulation of lymphocytes with autochthonous leukaemic cells alone induced cytotoxicity in 7/13 cases. In contrast, anti-leukaemic cytotoxicity was shown in 12/13 cases when responder lymphocytes were stimulated with both autochthonous leukaemic and unrelated allogeneic normal lymphocytes. The specificity of cytotoxicity was confirmed using other targets such as autochthonous PHA-transformed lymphoblasts and mouse L1210 cells. In 1/5 cases, CML remission lymphocytes stimulated with autochthonous leukaemic cells showed cytotoxicity to PHA-transformed autochthonous normal lymphoblasts, whilst 1/4 patients showed nonspecific cytotoxicity to L1210 cells when lymphocytes were cultured in MLC or MLTC, as well as in a 3-cell assay.